Habitat segregation in competing species of intertidal mussels in South Africa - Bownes, Sarah (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
Mytilus galloprovincialis is invasive on rocky shores on the west coast of South Africa where it has become the dominant intertidal mussel. The success of this species on the west coast and its superior competitive abilities, have led to concern that it may become invasive on the south coast at the expense of the indigenous mussel Perna perna. On shores where these species co-occur, there appears to be habitat segregation among zones occupied by mussels. M.galloprovincialis dominates the high-shore and P.perna the low-shore, with a mixed zone at mid-shore level. This study examined the factors responsible for these differences in distribution and abundance. The study was conducted in Plettenberg Bay and Tsitsikamma (70km apart) on the south coast of South Africa. Each site included two randomly selected locations (300-400m apart). A third mussel species, Choromytilus meridionalis, is found in large numbers at the sand/rock interface at one location in Plettenberg Bay. Aspects of settlement, recruitment, growth and mortality of juvenile and adult mussels were examined at different tidal heights at each site. Quantitative analysis of mussel population structure at these sites supported the initial observation of vertical habitat segregation. Post-larvae were identified to species and this was confirmed using hinge morphology and mitochondrial DNA analysis. Size at settlement was determined for each species to differentiate between primary and secondary settlement. Adult distribution of C.meridionalis was primarily determined by settlement, which was highly selective in this species. Settlement, recruitment and growth of P.perna decreased with increasing tidal height, while post-settlement mortality and adult mortality increased higher upshore. Thus all aspects of P.perna's life history contribute to the adult distribution of this species. Presumably, the abundance of P.perna on the high-shore is initially limited by recruitment while those that survive remain prone to elimination throughout adulthood. M.galloprovincialis displayed the same patterns of settlement and recruitment as P.perna. However, post-settlement mortality in this species was consistently low in the low and high zones. Juvenile growth also decreased upshore, suggesting that M.galloprovincialis may be able to maintain high densities on the high-shore through the persistence of successive settlements of slow-growing individuals. The low cover of M.galloprovincialis on the lowshore appeared to be determined by adult interactions. M.galloprovincialis experienced significantly higher adult mortality rates than P.perna in this zone. There were seasonal variations in the competitive advantages enjoyed by each species through growth, recruitment or mortality on the low-shore. In summer, P.perna had higher recruitment rates, faster growth and lower mortality rates, while M.galloprovincialis had slightly higher recruitment rates and faster growth rates in winter. P.perna is a warm water species while M.galloprovincialis thrives on the cold-temperate west coast of South Africa. Therefore both species appear to be at the edge of their optimal temperature regimes on the south coast, which may explain the seasonal advantages of each. Nevertheless, P.perna has maintained spatial dominance on the low-shore suggesting that it may ultimately be the winner in competition between these species. M.galloprovincialis appears to have a refuge from competition with P.perna on the high-shore due to its greater tolerance of desiccation stress, while being competitively excluded from the low-shore. Warm water temperatures coupled with poor recruitment rates at most sites may limit the success of M.galloprovincialis on this coast.
Keywords: Mussels -- South Africa Mussels -- Growth; Mussels -- Habitat -- South Africa; Mussels -- Larvae Perna -- South Africa; Mytilus galloprovincialis -- South Africa; Choromytilus meridionalis -- South Africa; Mytilidae -- South Africa